Advancing Backwards: Why Institutional Reform of German Federalism Reinforced Joint Decision-Making. Issue 1 (26th September 2017) - Benz, Arthur; Sonnicksen, Jared
Abstract: A series of recent reforms in German federalism have created a dynamic development unprecedented in the Federal Republic. They aimed at increasing federal and Länder governments' autonomy by decentralization and separating powers. Being negotiated in established structures of joint decision-making, significant change could hardly be expected. However, change evolved in a sequential process triggered by particular conditions: decisions of the constitutional court in the first federalism reform, the broader fiscal and economic crisis in the second, and a deadline to renovate the fiscal equalization scheme in the third. After first steps to decentralize powers, subsequent reforms reinforced cooperative federalism, but with an even stronger role of the federal government. Following a comparative-historical institutionalist perspective, the federal dynamics can be explained by the interplay of established institutions, routinized negotiation systems and different events triggering change. In contrast to the gradual evolution of cooperative federalism, these triggers caused unintended and contradictory effects.